Exenatide prevents statin-related LDL receptor increase and improves insulin secretion in pancreatic beta cells (1.1E7) in a protein kinase A-dependent manner - Buldak, Lukasz; Machnik, Grzegorz; Skudrzyk, Estera; Boldys, Aleksandra; Maliglowka, Mateusz; Kosowski, Michal; Basiak, Marcin; Buldak, Rafal Jakub; Okopien, Boguslaw (Journal of Applied Biomedicine, 2022)
Statins are primary drugs in the treatment of hyperlipidemias. This group of drugs is known for its beneficial pleiotropic effects (e.g., reduction of inflammatory state). However, a growing body of evidence suggests its diabetogenic properties. The culpable mechanism is not completely understood and might be related to the damage to pancreatic beta cells. Therefore, we conceived an in vitro study to explore the impact of atorvastatin on pancreatic islet beta cells line (1.1.E7). We evaluated the influence on viability, insulin, low-density lipoprotein (LDL) receptor, and proprotein convertase subtilisin/kexin type 9 (PCSK9) expression. A significant drop in mRNA for proinsulin and insulin expression was noted. Concurrently, a rise in LDL receptor at the protein level in cells exposed to atorvastatin was noted. Further experiments have shown that exenatide - belonging to glucagon-like peptide 1 (GLP-1) analogs that are used in a treatment of diabetes and known for its weight reducing properties - can alleviate the observed alterations. In this case, the mechanism of action of exenatide was dependent on a protein kinase A pathway. In conclusion, our results support the hypothesis that statin may have diabetogenic properties, which according to our study is related to reduced insulin expression. The concomitant use of GLP-1 receptor agonist seemed to successfully revert insulin expression.
Keywords: Hydroxymethylglutaryl-CoA Reductase Inhibitors; Cyclic AMP-Dependent Protein Kinases; Insulin Secretion; Exenatide; statiny; inzulin; beta-buňky; exenatid; sekrece inzulinu; proteinkinasy závislé na cyklickém AMP; LDL-receptory; Proprotein Convertase 9; Atorvastatin; Receptors, LDL; Insulin-Secreting Cells; Insulin; proproteinkonvertasa subtilisin/kexin typu 9; atorvastatin